Clonal drift demonstrates unexpected dynamics of the T-cell repertoire in T-large granular lymphocyte leukemia - Clemente, Michael J. (American Society of Hematology, 2011)
T-cell large granular lymphocyte leukemia (T-LGLL) is characterized by chronic lymphoproliferation of cytotoxic T lymphocytes (CTLs) and is associated with lineage-restricted cytopenias. Introduction of T-cell receptor (TCR) variable β-chain (Vβ) monoclonal antibodies has facilitated identification and enumeration of clonal CTLs by flow cytometry. A highly skewed TCR Vβ repertoire identified by flow cytometry is strongly associated with monoclonal CDR3 regions by quantitative sequencing and positive TCRγ rearrangement assays. Therefore, Vβ expansions can serve as surrogate markers of CTL clonality to assess clonal kinetics in T-LGLL. We analyzed the TCR repertoire in 143 patients, 71 of which were available for serial measurements over 6 to 96 months. Although the majority (38/71, 54%) maintained a consistent monoclonal expansion, many (26/71, 37%) unexpectedly displayed a change in the dominant clone, whereby the original CTL clone contracted and another emerged as demonstrated by Vβ typing. Our results demonstrate that the T-cell repertoire is more dynamic in T-LGLL than recognized previously, illustrating the heterogeneity of disorders under this categorization.